Alveolar Bone Regeneration by Transplantation of Periodontal Ligament Stem Cells and Bone Marrow Stem Cells in a Canine Peri‐Implant Defect Model: A Pilot Study - Su‐Hwan Kim; Kyoung‐Hwa Kim; Byoung‐Moo Seo; Ki‐Tae Koo; Tae‐Il Kim; Yang‐Jo Seol; Young Ku; In‐Chul Rhyu; Chong‐Pyoung Chung; Yong‐Moo Lee (2009)
Background: The present study was undertaken to evaluate the potential of periodontal ligament stem cells (PDLSCs) and bone marrow SCs (BMSCs) on alveolar bone regeneration in a canine peri‐implant defect model. Methods: Four adult, male beagle dogs were used in this study. Autologous BMSCs from the iliac crests and PDLSCs from extracted teeth were cultured. Three months after extraction, BMSC‐ and PDLSC‐loaded hydroxyapatite/β‐tricalcium phosphate (HA/TCP) (test groups) and cell‐free HA/TCP (control group) were implanted in three rectangular, saddle‐like peri‐implant defects, respectively. The left side of the mandible was initially prepared, and after 8 weeks, the right side was also prepared. The animals were sacrificed after an 8‐week healing period. Undecalcified ground sections were prepared. New bone formation and bone‐to‐implant contact (BIC) were measured histomorphometrically. BMSCs and PDLSCs were fluorescently labeled and traced. Results: Alveolar bone regeneration in surgically created peri‐implant saddle‐like defects was more effective in test groups than the control group. The BMSC group had the highest new bone formation (34.99% and 40.17% at healing times of 8 and 16 weeks, respectively) followed by the PDLSC group (31.90% and 36.51%) and control group (23.13% and 28.36%), respectively. Test groups exhibited a significantly higher new bone formation than the control group at 8 weeks, but the same was true for only the BMSC group at 16 weeks ( P <0.05). Fluorescently labeled cells were identified adjacent to HA/TCP carriers and, partly, near connective tissues and osteoids. Conclusion: This study demonstrated the feasibility of using stem cell–mediated bone regeneration to treat peri‐implant defects.